Notes for the development of a history of traditional Andean medicine - Devoto Bazán, Erick (2016)
Currently, growing numbers of Western medical practitioners consider traditional healing practices and treatments as less invasive and more effective. This is due largely to advances in research within the fi elds of history and anthropology.However, the historiography of Peruvian traditional healing practices has not been fully developed yet. This article examines some of the main contributions on this topic so far and provides a brief overview of written sources on Andean traditional medicine since pre-Hispanic times up to the present.